2011
DOI: 10.1042/bj20110376
|View full text |Cite
|
Sign up to set email alerts
|

Novel NADPH–cysteine covalent adduct found in the active site of an aldehyde dehydrogenase

Abstract: PaBADH (Pseudomonas aeruginosa betaine aldehyde dehydrogenase) catalyses the irreversible NAD(P)+-dependent oxidation of betaine aldehyde to its corresponding acid, the osmoprotector glycine betaine. This reaction is involved in the catabolism of choline and in the response of this important pathogen to the osmotic and oxidative stresses prevalent in infection sites. The crystal structure of PaBADH in complex with NADPH showed a novel covalent adduct between the C2N of the pyridine ring and the sulfur atom of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
19
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 42 publications
3
19
0
Order By: Relevance
“…example. Such an adduct was predicted by quantum mechanical calculations (27) and then characterized in two different structures from the ALDH family (17,23,28). However, to date, the functional role of the covalent adduct has remained elusive.…”
Section: Discussionmentioning
confidence: 99%
“…example. Such an adduct was predicted by quantum mechanical calculations (27) and then characterized in two different structures from the ALDH family (17,23,28). However, to date, the functional role of the covalent adduct has remained elusive.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, the inhibition of the binding of the reactive oxidized form NAD(P) by NAD(P)H was observed only for betaine aldehyde dehydrogenase from Pseudomonas aeruginosa (PaBADH) [21, 22]. The mechanism, by which the enzyme differentiates the oxidation states of the coenzyme, is not fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…For the ordered Bi Bi reaction mechanism, substrate inhibition can be caused by the binding of excess substrate to the enzyme-NAD(P) ϩ complex (13,45). Therefore, we performed a UV scanning analysis (280 to 400 nm) of BetB to detect a thio-adduct between its cysteine (Cys289 in BetB) and the pyridine ring of NAD ϩ , which has a typical absorbance peak at 325 nm (8). How- ever, the addition of NAD ϩ to BetB did not result in the increase in absorbance around 325 nm (data not shown), which is consistent with the absence of BetB inhibition by NAD ϩ and suggests that the BetB inhibition is not caused by the formation of a thio-adduct.…”
Section: Location Of Residuesmentioning
confidence: 99%
“…In contrast, the P. aeruginosa BADH (PaBADH, ALDH9) follows a random Bi Bi mechanism, although the mechanism is predominantly ordered in the case of the NADP ϩ -dependent reaction (35). A kinetic study revealed that the activity of PaBADH is inhibited by the cofactor and partially by the aldehyde (25,35), and the structure of this enzyme in complex with the cofactor suggested that this inhibition is caused by a novel NADPH-cysteine covalent adduct (8).…”
mentioning
confidence: 99%
See 1 more Smart Citation